(untitled) (Вестник КазНУ. Серия Экономическая, 2017)
Green technologies are essential tools to ensure sustainable development of the economy. The transition to a green economy requires changes in existing governance approaches, institutions, and markets. One of the important indicators is a successful implementation of research results in green technologies. In this regard, the author analyzed green technology projects in Kazakhstan in terms of commercialization. Research objectives are to patent analysis of projects and to identify key factors and barriers that affect the successful commercialization of technologies based on the respondents’ opinions. Interviews with representatives of 14 green technology projects and 9 experts were conducted and analyzed. In the result of total 23 interviews factors and barriers affecting the commercialization of green technologies in Kazakhstan were identified. The overwhelming majority of experts emphasized the importance of financial, infrastructural, technological and personnel factors. It is necessary to take into account all mentioned factors and develop complex measures to overcome barriers. That would be basis for successful of transition from “brown” to green economy.